Elements of Success How Type of Secondary Education Credential Helps Predict Enlistee Attrition - Burkhauser, Susan (RAND Corporation, 2014)
The U.S. military services have traditionally used a tiering system including education credentials as one element of gauging the likelihood of a recruit persevering through his or her first term of service. To assess the continuing value of this system, the authors compared attrition rates for those with distance learning or homeschool credentials to those of high school diploma holders.